Communicating with children and their families : responding to need and protection - Davies, Liz, 1948-; Lebloch, Evelyn Kerrigan (Maidenhead : Open University Press, 2013)
Good communication skills are essential for effective social work practice. This book brings current, relevant and contested areas of social work practice to life by using scripts from real life situations to demonstrate every day scenarios social workers encounter when communicating with children and their families. Each chapter takes a key aspect of communication: engagement; negotiation; investigation; use of power and persistence and presents it in a context of good professional practice. It also examines the common pitfalls that workers could fall into and contextualises the script through comparison with a contemporary case study. Relevant theoretical frameworks, legislation, policy and ethical dilemmas are included for each situation. This engaging and innovative book gives social work students and professionals a thorough understanding of the best ways to communicate with children and their families in complex and challenging situations. The book also has relevance to other professionals such as those working in health, education, police and the voluntary sector. -- Publisher website.
Erratum inserted.
Includes bibliographical references (p. [186]-198) and index.
Keywords: Social service; Communication